Mechanism of the reactions of ruthenium(II) polypyridyl complexes with thiourea, sulfur-containing amino acids and nitrogen-containing heterocycles - Puchta, Ralph; Bugarčić, Živadin D.; et al. (Polyhedron, 2015)
Abstract The substitution reactions of ruthenium(II) polypyridyl complexes [Ru(Cl-tpy)(en)Cl][Cl] (1) and [Ru(Cl-tpy)(dach)Cl][Cl] (2) (Cl-tpy = 4′-chloro-2,2′:6′,2″-terpyridine, en = 1,2-diaminoethane, dach = 1,2-diaminocyclohexane), with sulfur- (thiourea, l-cysteine and l-methionine) and nitrogen-donor (pyrazole, 1,2,4-triazole and pyridine) biomolecules were studied in aqueous solutions (25 mM Hepes buffer, 30 mM NaCl, pH 7.4) by UV-Vis spectrophotometry. The aim of the study was to improve the understanding of the mechanism of action of ruthenium(II) terpyridine complexes as potential antitumor drugs. The rate of the reaction of 1 and 2 with selected ligands depends on the nature and on the charge of both the chelating and the entering ligand. The order of reactivity of investigated ligands is: thiourea > l-cysteine > pyrazole > 1,2,4-triazole > pyridine > l-methionine. The measured enthalpies and entropies of activation (ΔH≠ > 0, ΔS≠ < 0) support an associative mechanism for the substitution process. The interaction of these ruthenium(II) polypyridyl complexes with the studied ligands was also investigated by 1H NMR spectroscopy. All reactions lead, although with different rates and to different extents, to the formation of monofunctional adduct. The NMR results have revealed redox reactions of thiol adducts [Ru(Cl-tpy)(en)(SR)]+ (4) and [Ru(Cl-tpy)(dach)(SR)]+ (11) induced by Ru(II) coordination forming the sulfenato complexes [Ru(Cl-tpy)(en)(RSO)]2+ (5) and [Ru(Cl-tpy)(dach)(RSO)]2+ (12). The results from the kinetic studies were supported also by density functional theory calculations (B3LYP/LANL2DZp), which showed that guanine coordination to the ruthenium(II) terpyridine complexes is much more favored than thioether coordination. DFT calculations revealed also that the N4 coordination of 1,2,4-triazole (Tz) to the ruthenium center leads to more stable species compared to the N2 coordination, which is in accordance with the NMR findings.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Amino acids; DFT calculations; Heterocycles; Kinetics; Ru(II) complexes